Antibacterial Activity of Bandotan (Ageratum conyzoides L) Leaves Extracts Against Methicillin-Resistant Staphylococcus aureus - Selvira Anandia Intan Maulidya; Doni Anshar Nuari; Shendi Suryana; Sumia Almarifah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of nosocomial infections throughout the world and can be life-threatening as well. This study aimed to determine the antibacterial activity of Bandotan (Ageratum conyzoides L) leaves ethanolic extract against MRSA's growth. Ageratum conyzoides leaves were extracted by ethanol and screened for their phytochemical constituent. Ethanolic extracts of A. conyzoides leaves were evaluated for their potential antibacterial activity using disc diffusion assay. The minimum inhibitory concentration (MIC) value was determined using the agar dilution method. Phytochemical screening shows that the extracts contain alkaloids, flavonoids, saponins, tannins, and steroids or triterpenoids. Ageratum conyzoides leaves extract shows a 25.1 mm inhibitory zone at 12.5% extract concentration with MIC value equivalents to 4.46 x 10-6 g of gentamicin. This study concludes that A. conyzoides leaves ethanolic extracts have potential antibacterial activity against MRSA.